Artificial Intelligence in Learning Transformation: Opportunities and Challenges for Educational Technology - Dewi Nurmalasari; Yatim Riyanto; Lamijan Hadi Susarno (Journal on Smart Learning Technologies, 2026)
The development of digital technology has significantly transformed the learning paradigm, particularly with the emergence of Artificial Intelligence (AI), which plays an important role in transforming educational systems. AI offers opportunities to create adaptive, personalized, collaborative, and data-driven learning environments that place students at the center of the learning process. This study aims to analyze the role, opportunities, and challenges of implementing Artificial Intelligence in the field of educational technology as an effort to support the transformation of 21st-century learning. This research employs a qualitative approach using a library research method by examining various academic sources such as reputable journals, scientific books, and other relevant literature. The analysis was conducted through thematic synthesis of previous research findings to identify patterns of AI implementation in learning design, processes, and evaluation, as well as its implications for the development of educational technology. The results indicate that AI has great potential to improve learning effectiveness through adaptive learning systems, learning data analytics, and automated assessments that provide fast and accurate feedback. In addition, AI enables more personalized learning experiences based on students’ needs and learning characteristics. However, the implementation of AI in education still faces several challenges, including data privacy issues, algorithmic bias, human resource readiness, and the digital divide across regions. Overall, Artificial Intelligence functions as a catalyst for educational transformation that requires a balance between technological advancement and human values. The successful implementation of AI depends on educators’ digital literacy, ethical data governance, and cross-sector collaboration in building an intelligent, inclusive, and sustainable learning ecosystem.